O comportamento feminino no romance romântico do século XIX: a idealização romântica de Mariana, em Amor de Perdição, de Camilo Castelo Branco - BRAGA, Rosiléia Batista (2024)
his work titled as female behavior in the romantic novel of the 19th century: the romantic idealization of Mariana, in Amor de Perdição, by Camilo Castelo Branco, instigated me since high school, when I got to know the romance romantic author, and the literary school to which he belonged. in it will be outlined a brief study of the author and the plot itself, highlighting the characteristics evident in the text, in what concerns the character Mariana, through excerpts, in which if such aspects are observed, and still raising considerations of her attitudes, relating to this, the evidence with the profiles of women in the nineteenth century and present. These behaviors, which are widespread for historical reasons, political, cultural and economic. And, finally making a parallel with the female behaviors throughout history and how this paradigm was deconstructed of patriarchal society over time. In this sense, literature is an important instrument to rethink principles and values ​​taken as absolute, in the case of this theme, specifically with regard to the universe of women. Having as theoretical contribution to bibliographical research based on Massaud Moisés, Jacó Guinsburg among others, which prove the veracity of the study.